MODEL PEMBELAJARAN KARAKTER DI PONDOK PASANTREN - Dr. Mardyawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
Character development as one of the priority programs of national development which is implicitlyaffirmed the National Long-Term Development Plan (RPJPN) 2005-2025. Therefore, to realize it inaccordance with the national culture is certainly not solely carried out in schools and Pasantrenthrough a series of teaching and learning activities outside of school, but also through habituation(habituation) in life. This is the main basis so it is said that education is the Pondok Pasantren easierto form the character of students as learning models that do more dominant model of learningthrough habituation. Eg learning model halaqah, methods sorogan, Weton, Muhawarah,Mudzakarah, Memory, Demonstration. This model was developed at the Pondok Pasantren learningand being able to shape the character of the students. As is understood that the character is "a way ofthinking and behaving that is characteristic of each individual to live and work, both in the sphere offamily life, community, nation, and state. Similarly, education is "the process of changing attitudesand code of conduct of a person or group of people in a mature business man through the efforts ofteaching and training, processes, means, acts educate. By looking at the second definition above thecharacter and education which are referred to implementation of character education can be seen inthe Pondok Pasantren the realization of quality education and teaching towards the creation of amoral generation, skilled and independent and can be basic community development. Thus it can beunderstood that learning on Pondok Pasantren has implemented character education since firstlearning model halaqah which is the process of formation of a way of thinking and behaving studentsand characterizes them in private life, family, community, and environment.